Genetic and phenotypic variation among Galaxias maculatus populations reflects contrasting landscape effects between northern and southern Patagonia - Carrea, Cecilia (2013)
1. Understanding the influence of landscape characteristics on genetic and phenotypic intraspecific variability can yield insights into how evolutionary processes work as well as provide essential information for the conservation of biodiversity. 2. Our aim was to compare the genetic structure and phenotypic variation among Galaxias maculatus populations inhabiting two Atlantic Ocean river basins in Patagonia in relation to historical and contemporary landscape characteristics associated with latitude. 3. Population genetic analysis (based on eight microsatellite loci, 505 individuals) indicates that genetic structure is more pronounced in the Rı´o Negro basin (RN) at 39?41S (10 localities) than in the southernmost Santa Cruz River basin (SCR) at 49?50S (seven localities). Spatial autocorrelation analysis showed different effects of geographic distance in shaping population differentiation patterns in the two basins. 4. While in northern Patagonia, fragmented populations could have survived the severity of Quaternary climate cycles, at higher latitudes G. maculatus populations were probably extirpated by extensive ice sheets. Extant populations in the upper reaches of the southernmost basin probably originated from refugia close to the Atlantic Ocean. 5. Based on otolith microchemistry, we have documented facultative diadromy for the first time for the species in the SCR basin, while no evidence of migration to the sea was found in individuals from the RN basin. Vertebral number increased with latitude, and within the SCR basin, the higher counts are possibly associated with a migratory life style.